Ternary tin selenium sulfide (SnSe0.5S0.5) nano alloy as the high-performance anode for lithium-ion and sodium-ion batteries. (November 2017) - Tang, Qiming; Cui, Yanhui; Wu, Junwei; Qu, Deyang; Baker, Andrew P.; Ma, Yiheng; Song, Xiaona; Liu, Yanchen
Abstract: Metal sulfides have received tremendous attention due to their superior electrochemical performance. In this study, it is the first time that the ternary tin selenium sulfide, SnSe0.5 S0.5, is investigated as a potential high-performance anode material for lithium-ion batteries (LIBs) and sodium-ion batteries (SIBs). The SnSe0.5 S0.5 /C nanocomposites have also been synthesized through a facile polyol-method followed by a simple hydrothermal process and subsequent sintering. The material demonstrated a high specific capacity and a long-term cycling stability in both Li-ion and Na-ion batteries (625 mA h g −1 for LIB at 500 mA g −1 rate after 1000 cycles, 430 mA h g −1 in a SIB at 200 mA g −1 rate after 100 cycles). Furthermore, the kinetic analysis of Li-ions and Na-ions storage revealed that the extrinsic pseudocapacitive contribution could improve the charge transfer rate during the insertion and extraction of Li-ion and Na-ion, thus enhancing the rate performance and cycling stability. These results demonstrated that the novel tin selenium sulfide (SnSe0.5 S0.5 ) material could potentially be an excellent anode material for Li-ion storage and Na-ion storage. Graphical abstract: A new anode material for Li-ion and Na-ion batteries is synthesized via a facile polyol-method and hydrothermal process. It consists of SnSe0.5 S0.5 nano alloy encapsulated in carbon bulk and surrounded by carbon spheres. A high specific capacity and excellent cycling stability are achieved (625 mA h g −1 for LIB at 500 mA g −1 rate after 1000 discharge/charge cycles, and 430 mA h g −1 in a SIB at 200 mA g −1 rate after 100 cycles). Highlights: A new anode material, SnSe0.5 S0.5 /C nanocomposite, was synthesized. As anode for LIB, it delivers capacity of 625 mA h g −1 at 1000th cycles. As anode for SIB, it delivers 430 mA h g −1 at 100th cycles. Pseudocapacitive behavior in electrode could improve the charge transfer.